Crizotinib efficacy in alk-positive advanced stage non-small cell lung cancer patients: A real-world experience from Turkey - Kılıçkap, Sadettin; Öztürk, Akın; Karadurmuş, Nuri; Korkmaz, Taner; Yumuk, Perran Fulden; Çiçin, İrfan; Paydaş, Semra; Çılbır, Ebru; Sakalar, Teoman; Uysal, Mükremin; Üskent, Necdet; Demir, Nurcan; et al. (Elsevier Science Inc, 2018)
Background: Increasing evidence leads to a ratiocination that genetic heterogeneity of the lung adenocarcinoma patients with sensitive EGFR mutations may impact clinical responses and outcomes to EGFR-TKIs. Method: We performed targeted NGS with a gene panel covering 416 cancer-related genes to profile genetic characteristics of 69 lung adenocarcinoma patients with activating EGFR mutations and assessed the contribution of targeted NGS to exploration of genetic heterogeneity of such cohort. Result: We detected total 200 actionable genetic alterations (mean 2.9 variations per patient, range: 1-7 variations) in tumor DNA and 140 actionable genetic alterations (mean 2.0 variations per patient, range: 0-5 variations) in matched plasma ctDNA, respectively. The concurrent genes with the highest mutation rate were TP53 (observed in 72.5% patients), other uncommon EGFR mutations (observed in 21.7% patients), EGFR amplification (observed in 20.3% patients), RB1 (observed in 10.1% patients), PIK3CA (observed in 7.2% patients), and MYC (observed in 5.8% patients). NGS provides EGFR mutation detection in plasma with a test sensitivity of 88.2% and specificity of 100.0%.
WOS: 000454014501235
Keywords: NSCLC; ALK Inhibitor; Crizotinib